Eligibility for PCSK9 inhibitors based on the 2019 ESC/EAS and 2018 ACC/AHA guidelines. (20th July 2020) - Koskinas, Konstantinos C; Gencer, Baris; Nanchen, David; Branca, Mattia; Carballo, David; Klingenberg, Roland; Blum, Manuel R; Carballo, Sebastian; Muller, Olivier; Matter, Christian M; Lüscher, Thomas F; Rodondi, Nicolas; et al.
Abstract: Aims: The 2018 American College of Cardiology (ACC)/American Heart Association (AHA) and 2019 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) lipid guidelines recently updated their recommendations regarding proprotein convertase subtilisin/kexin-9 inhibitors (PCSK9i). We assessed the potential eligibility for PCSK9i according to the new guidelines in patients with acute coronary syndromes. Methods and results: We analysed a contemporary, prospective Swiss cohort of patients hospitalised for acute coronary syndromes. We modelled a statin intensification effect and an incremental ezetimibe effect on low-density lipoprotein-cholesterol levels among patients who were not on high-intensity statins or ezetimibe. One year after the index acute coronary syndrome event, treatment eligibility for PCSK9i was defined as low-density lipoprotein-cholesterol of 1.4 mmol/l or greater according to ESC/EAS guidelines. For ACC/AHA guidelines, treatment eligibility was defined as low-density lipoprotein-cholesterol of 1.8 mmol/l or greater in the presence of very high-risk atherosclerotic cardiovascular disease, defined by multiple major atherosclerotic cardiovascular disease events and/or high-risk conditions. Of 2521 patients, 93.2% were treated with statins (53% high-intensity statins) and 7.3% with ezetimibe at 1 year, and 54.9% had very high-risk atherosclerotic cardiovascular disease. Low-density lipoprotein-cholesterol levels less than 1.8 mmol/l and less than 1.4 mmol/l at 1 year were observed in 37.5% and 15.7% of patients, respectively. After modelling the statin intensification and ezetimibe effects, these numbers increased to 76.1% and 49%, respectively. The proportion of patients eligible for PCSK9i was 51% according to ESC/EAS criteria versus 14% according to ACC/AHA criteria. Conclusions: In this analysis, the 2019 ESC/EAS guidelines rendered half of all post-acute coronary syndrome patients potentially eligible for PCSK9i treatment, as compared to a three-fold lower eligibility rate based on the 2018 ACC/AHA guidelines.